ANALISIS PENGARUH PENERAPAN SISTEM E-FILING TERHADAP KEPATUHAN WAJIB PAJAK DENGAN SOSIALISASI PERPAJAKAN SEBAGAI VARIABEL MODERASI PADA DESA PEMATANG SERAI TANJUNG PURA LANGKAT - Susilawaty, Tengku Eka; Damanik, Destari Nurlaila (JURNAL PERPAJAKAN, 2021)
The purpose of study was to analyze the influence of E-Filing System Application to Taxpayer Compliance with Taxation Socialization as a Moderation Variable. This research data was obtained from questionnaire (Primary) distributed to the community of Pematang Serai Village Tanjung Pura Langkat using probability sampling method. The population of this research is the people of Pematang Serai Village, Tanjung Pura Langkat, who came during the research at BUMDES Mozaik, Pematang Serai Village, Tanjug Pura Langkat. The sample used in this study were 99 respondents. This questionnaire was tested with validity test and reliability test before the study. The classic assumption tests used are the normality test, the multicollinearity test, the heteroscedasticity test, and the linearity test. Hypothesis testing used is simple linear regression and Moderated Regression Analysis. The results of this study indicate that Application of the E-Filing System has a significant effect on Taxpayer Compliance. The Socialization of Taxation strengthens the influence of the application of the E-Filing System to Taxpayer Compliance.